Continuous dual of c_0(Z,X,λ, p) and c(Z,X,λ, p) - Srivastava, J. K.; Agrawal, R. (Methods of Functional Analysis and Topology, 2014)
A bilateral sequence is a function whose domain is the set Z of all integers with natural ordering. In this paper we study the continuous dual of the Banach space of X-valued bilateral sequence spaces c_0(Z,X,λ, p) and c(Z,X,λ, p).